Aleurocyperus humus gen. et sp. n. (Hemiptera: Aleyrodidae) from Taiwan, with interesting feeding behaviour - Ko, Chiun-Cheng; Dubey, Anil Kumar (Zootaxa, 2007)
Aleurocyperus humus gen. et sp. n. is described from Taiwan, feeding on Cyperus rotundus, Kyllinga brevifolia and Torulinium odoratum (Cyperaceae), also Eleusine indica (Poaceae), with illustrations of the egg, immature stages, adult male and female. The new genus is defined through a combination of tracheal furrows, marginal characters, placement of dorsal setae, and absence of first abdominal setae. Observations are also presented on feeding behaviour.